Caracterização físico-química e desempenho de motor gerador operando com blendas de diesel/ óleo de crambe - Reis, Leonardo da Silva (2022)
The continuous use of petroleum derivatives appears as one of the great polluting agents of the environment. The exponential increase in population and technological advances increasingly demand renewable energy sources. Biodiesel, from an environmental point of view, is a biodegradable, non-toxic, carbon neutral product used worldwide. Thus, the present work aimed to improve the continuous mechanical pressing process in a mechanical press, evaluating the effect of the independent variables of extraction temperature and the moisture content added to the crambe grains on the crude oil extraction yield. The completely randomized design (DIC) will be carried out with three replications, thus, each mechanical extraction of the oil was divided into four relative moisture contents of water added to the samples at the temperature ranges for the extraction of oil and crambe cake. Crambe oil will be evaluated through viscosity, specific mass and flash point. It will also be evaluated the quality of mixtures of biodiesel from crambe with diesel oil, in different proportions, through the physical-chemical parameters, engine-generator performance, together with the analysis of emissions generated in the process. The tests took place under a completely randomized design, with four demands of resistive electrical loads of powers 500W, 1500W, 4500W and 6000W and eight concentrations of B0 fuels as control B5, B10, B15, B20, B50, B70 and B90. Biodiesel was produced through the transesterification of oil. The physicochemical properties of the blends were analyzed in a specialized laboratory. According to the results, the viscosity, the specific mass and the flash point increased, with the addition of biodiesel to diesel, there was a reduction in CO₂, NO₂ and CO. It can be said that the B20 blend had a better result of the Biodiesel oil compared to the other blends, the research showed that the burning of the B20 showed more efficiency.